KERJASAMA OTORITAS PAJAK DAN OTORITAS ANTI KORUPSI DALAM UPAYA MENINGKATKAN KEPATUHAN PAJAK - Matabean, Redhy; Juwono, Vishnu (Scientax, 2019)
Tax crimes and corruption have caused huge losses in various countries. Therefore, one of the emphases of the Sustainable Development Goals is how to reduce corruption substantially in all its forms. Corruption and tax crimes can be interrelated. Hence, appropriate policies are needed from the tax authorities and anti-corruption authorities in handling them. This study aims to discover the collaboration design in dealing with tax crimes and corruption. The analysis results illustrate that systematic design can be carried out through collaboration between tax authorities and anti-corruption authorities by considering three aspects. The first aspect is identifying tax non-compliance behaviour, the second is identifying tax crime and corruption indicators, while the third aspect is determining the form of collaboration needed. This study also opens up opportunities for collaboration in the form of information exchange by the Directorate General of Taxes and the Corruption Eradication Commission through a tax monitoring and public complaints database and state administrators’ assets report.